Cardiorespiratory fitness levels and their association with cardiovascular profile in patients with rheumatoid arthritis: a cross-sectional study. (25th July 2015) - Metsios, George S.; Koutedakis, Yiannis; Veldhuijzen van Zanten, Jet J. C. S.; Stavropoulos-Kalinoglou, Antonis; Vitalis, Panagiotis; Duda, Joan L.; Ntoumanis, Nikos; Rouse, Peter C.; Kitas, George D.
Abstract: Objective. The aim of this study was to investigate the association of different physical fitness levels [assessed by the maximal oxygen uptake (VO2 max) test] with cardiovascular disease (CVD) risk factors in patients with RA. Methods. A total of 150 RA patients were assessed for cardiorespiratory fitness with a VO2 max test and, based on this, were split in three groups using the 33rd (18.1 ml/kg/min) and 66th (22.4 ml/kg/min) centiles. Classical and novel CVD risk factors [blood pressure, body fat, insulin resistance, cholesterol, triglycerides, high-density lipoprotein (HDL), physical activity, CRP, fibrinogen and white cell count], 10-year CVD risk, disease activity (DAS28) and severity (HAQ) were assessed in all cases. Results. Mean VO2 max for all RA patients was 20.9 (s.d. 5.7) ml/kg/min. The 10-year CVD risk ( P = 0.003), systolic blood pressure ( P = 0.039), HDL ( P = 0.017), insulin resistance and body fat (both at P < 0.001), CRP ( P = 0.005), white blood cell count ( P = 0.015) and fibrinogen ( P < 0.001) were significantly different between the VO2 max tertiles favouring the group with the higher VO2 max levels. In multivariate analyses of variance, VO2 max was significantly associated with body fat ( P < 0.001), HDL ( P = 0.007), insulin resistance ( P < 0.003) and 10-year CVD risk ( P < 0.001), even after adjustment for DAS28, HAQ and physical activity. Conclusion. VO2 max levels are alarmingly low in RA patients. Higher levels of VO2 max are associated with a better cardiovascular profile in this population. Future studies need to focus on developing effective behavioural interventions to improve cardiorespiratory fitness in RA.